Um estudo da aplicação do Lean Ux em pequenas equipes com rotatividade para o desenvolvimento de interface no contexto universitário - Beux, Jucelia Giacomelli (2019)
Interfaces development applying methods that take in consideration user experience is increasingly evident in organizations. However, it is a diferente reality in smaller teams that have high turnover of members, as it happens in the university context, where, in many cases, the development teams linked to the research groups are formed by researchers, undergraduate and graduate students. The students are linked with the project during the period of theirs courses or scholarships. From this perspective, this paper developed a multiplatform interface for the DSSAT Suite applying the Lean UX method. The DSSAT Suite system is maintained by the DSSAT Foundation and focuses on the agricultural area. This interface, used as a case study for the application of Lean UX, was developed by the Mosaico research group, in the University of Passo Fundo, which is characterized as a small team with high turnover of members. The application of the Lean UX method aimed to present improvements for the developing of the projects maintained by the group, adopting a standardization of development, aiming to improve the final quality of the systems developed. For this application of Lean UX, two versions were developed for the interface, the first without and the second with the application of the method. For the analysis of the results, the techniques of observation and questionnaire were used. As result, improvements were observed in the execution time of the experiments in the new interface, as well as increased user satisfaction, using the interface, which was considered more intuitive, agile and clean. Finally, in relation to the development team, there was evidence of greater satisfaction and greater engagement in the development of the project.